М.І. Туган-Барановський – теоретик кооперативного руху (до 150-річчя від дня народження) - Половець, В. (Сiверянський лiтопис, 2015)
Стаття присвячена визначному вченому-економісту, наукова спадщина якого має
не тільки велике теоретичне значення, але й дає всі підстави стверджувати про її виключно прагматичну роль для виховання національної свідомості широких народних мас, залучення здобутків попередніх поколінь суспільства для вступу у складний світ
дії економічних заходів та ринкових відносин. Статья посвящена видному учёному-экономисту, научное наследие которого имеет
не только большое теоретическое значение, но и даёт все основания утверждать о её
исключительно прагматической роли для воспитания национальной сознательности
широких народных масс, приобщения достижений предыдущих поколений общества при
вступлении в сложный мир действия экономических законов и рыночных отношений. Mikhail Ivanovich Tugan-Baranovsky’s scholarly legacy is about 140 works which cover
almost all areas of economics. Most important is his theory of periodic crises, to the study of
which he has devoted a number of works published also in German and French translations
and which brought him world renown. Based on the concept of business cycles studied by
M. Tugan-Baranovsky, a standing committee for prediction of industrial crises acted in France.
Equally popular was his dualistic theory of value, based on a critique of the labour theories
of David Ricardo and Karl Marx, and of the marginal utility theory of the Austrian School
of economics. Professor Tugan-Baranovsky has devoted much attention to the development of cooperative theory, through the study of which he became one of the most prominent
theoreticians of the cooperative movement in Europe.